Analysis of Tweed’s facial triangle in mixed dentition children with class III malocclusion treated by two different appliances - Fareen, Nashid; Alam, Mohammad Khursheed; Khamis, Mohd Fadhli; Mokhtar, Norehan (2017)
Reverse twin-block (RTB) and reverse pull face mask (RPFM) are two commonly used orthodontic appliances to treat Class III malocclusions in mixed dentition children.